Characterization of the optical gain in erbium-ytterbium-doped zinc and sodium-zinc phosphate glasses - Rivera, Frida Lissete Flores; Velázquez, Dulce Yolotzin Medina; Aldaya, Ivan [UNESP]; Pérez-Sánchez, Grethell Georgina (Optica Publishing Group, 2022)
Glasses doped with rare-earth elements represent a key-enabling amplification technology for fiber-based systems and integrated devices. Even if silica has been the preferred glass matrix for optical amplifiers, some other glasses have been proposed as an alternative. Phosphates, in particular, present a lower glass transition temperature and have a structure that envisages a capacity to host erbium and ytterbium dopants. In this paper, we characterize the gain of zinc and sodium zinc phosphate doped either only with erbium or with erbium and ytterbium. The experimental results reveal that, among the different considered configurations, the sodium zinc phosphate with erbium-ytterbium co-doping leads to an on-off gain coefficient as large as 40 dB/cm.